Analisis Finansial Distress Untuk Memprediksi Risiko Kebangkrutan Perusahaan Sub Sektor Energi - Pauline Cielo; Gusganda Suria Manda (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine and analyze the financial performance of the energy sub-sector using the Almant Z-Score method. This research is a quantitative descriptive study. The population in this study are energy sub-sector companies listed on the Indonesia Stock Exchange 2015-2019. The sample in this study amounted to 4 energy sub-sector companies, namely PT. Perusahaan Gas Negara, PT. Leyand International, PT. Rukun Raharja, and PT. Mitra Energi Persada. The sampling technique in this study was using purposive sampling technique. The results of the financial distress predictions for the energy sub-sector companies, amounting to 4 publicly traded companies during the 2015 to 2019 research period using the Altman Z-Score method. This results in three companies in financial distress and one company in a safe area. Keywords: Finansial Distress, Bankrupty, Energy Sub-sector